Quality midwifery care during childbirth at a midwife obstetric unit: A qualitative study - Martin, Sedeeka; Filies, Gérard C.; Robertson, Anneline E. (Curationis (Pretoria), 2025)
Background Globally, there is an increasing focus on enhancing the quality of midwifery care. In public institutions, primary care midwifery is provided at a midwife obstetric unit (MOU). Midwives at MOUs are the first contact that pregnant women have when accessing midwifery care. There exists a notable disparity in the perception of quality midwifery care between midwives and women. In South Africa, there has been a scarcity of research examining the perspectives of midwives and women, regarding the quality of midwifery care provided during childbirth. Objectives The objective of this study was to explore and describe women’s and midwives’ perceptions of the quality of midwifery care during childbirth, at a MOU in Cape Town in the Western Cape, South Africa. Method A qualitative exploratory descriptive design was utilised. Four women and five midwives were selected through purposive sampling. Semi-structured interviews were undertaken, transcribed and analysed utilising Tesch’s eight-step approach to qualitative data analysis. Results Three themes emerged: (1) understanding of quality midwifery care, (2) experiences of women during childbirth and (3) support received by women and midwives. Conclusion The quality of midwifery care remains compromised within the MOU setting due to various challenges encompassing limitations of both human and physical resources. It is imperative to establish a shared understanding of what constitutes quality midwifery care, as women and midwives often perceive it differently. Contribution Midwifery care during childbirth requires the engagement of all stakeholders, including women, to enhance the quality of midwifery care provided.